Creation of Silicon-Vacancy Color Centers in Diamond by Ion Implantation - Lagomarsino, S.; Flatae, A. M.; Kambalathmana, H.; Sledz, F.; Hunold, L.; Soltani, N.; Reuschel, P.; Sciortino, S.; Gelli, N.; Massi, M.; Czelusniak, C.; Giuntini, L.; et al. (Frontiers in Physics, 2021)
Silicon-vacancy (SiV) centers in diamond are gaining an increased interest for application, such as in quantum technologies and sensing. Due to the strong luminescence concentrated in its sharp zero-phonon line at room temperature, SiV centers are being investigated as single-photon sources for quantum communication, and also as temperature probes for sensing. Here, we discussed strategies for the fabrication of SiV centers in diamond based on Si-ion implantation followed by thermal activation. SiV color centers in high-quality single crystals have the best optical properties, but polycrystalline micro and nanostructures are interesting for applications in nano-optics. Moreover, we discuss the photoluminescence properties of SiV centers in phosphorous-doped diamond, which are relevant for the creation of electroluminescent devices, and nanophotonics strategies to improve the emission characteristics of the SiV centers. Finally, the optical properties of such centers at room and high temperatures show the robustness of the center and give perspectives for temperature-sensing applications.